How to protect the proximal bronchial tree during stereotactic radiotherapy of ultracentral lung tumors: Lessons from MR-guided treatment - Sebastian Regnery; Efthimios Katsigiannopulos; Hin Lau; Philipp Hoegen-Saßmannshausen; Fabian Weykamp; Claudia Katharina Renkamp; Carolin Rippke; Fabian Schlüter; Sophia Albert; Jan Meis; Marietta Kirchner; Alexandra Balzer; et al. (Clinical and Translational Radiation Oncology)
Purpose: To use imaging data from stereotactic MR-guided online adaptive radiotherapy (SMART) of ultracentral lung tumors (ULT) for development of a safe non-adaptive approach towards stereotactic body radiotherapy (SBRT) of ULT. Patients and Methods: Analysis is based on 19 patients with ULT who received SMART (10 × 5.0–5.5 Gy) on a 0.35 T MR-Linac (MRIdian®) in the prospective MAGELLAN trial. 4D-planning CT data of six patients served to quantify proximal bronchial tree (PBT) breathing motion. Daily fraction MRIs are used to calculate interfractional translations (mediolateral (ML), anterior-posterior (AP), superior-inferior (SI)) and their dosimetric consequences for the PBT. A planning risk volume (PRV) is calculated for an assumed non-adaptive SBRT in deep-inspiration breath hold (DIBH) with surface-guidance (AlignRT®). Finally, non-adaptive volumetric modulated arc (VMAT) SBRT is simulated with and without a PRV for N = 10 patients (10 × 5.5 Gy). Results: The PBT shows relevant breathing motion, especially in superior-inferior direction (median ML: 2.5 mm, AP: 1.9 mm and SI: 9.2 mm). Furthermore, moderate interfractional translations are observed (mean absolute translation ML: 1.3 mm, AP: 1.3 mm, SI: 1.1 mm), with an estimated 2 mm PRV margin for interfractional changes alone. Simulated non-adaptive SBRT leads to PBT overdoses in 60 % of patients (median overdosed fractions VMAT: 2.5, predicted MR-linac plans 4). Both MR-guided online plan adaptation (SMART) and PRV-based non-adaptive VMAT prevent PBT overdoses, but SMART yields significantly higher planning target volume (PTV) coverage (SMART: median 96 % [IQR 95–96], VMAT: median 89 % [IQR 77–94], p = 0.014). Conclusions: Both intrafractional breathing motion and interfractional translations may impact doses to the PBT during SBRT of ULT. SMART protects the PBT from overdoses while maintaining high PTV coverage. Non-adaptive SBRT appears safe with advanced breathing motion management and PRV, but yields inferior PTV coverage.